The role of lipid traits in mediating the effect of body mass index on serum urate - Peng, Liuqing; Jing, Jiarui; He, Simin; Wang, Juping; Gao, Xue; Wang, Tong (Frontiers in Endocrinology, 2022)
Objective To explore whether total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoprotein (LDL), and triglyceride (TG) are mediators in the pathway of body mass index (BMI) on serum urate and determine the proportion of the mediation effect. Methods This study used observational and two-sample Mendelian randomization (MR) analyses to explore the mediation effects of TC, HDL, LDL, and TG in the pathway of BMI on serum urate. We determined the size and the extent to which these lipids mediate any effect of BMI on serum urate. Results Observational analysis results showed that HDL and TG can partially explain the association of BMI on serum urate, and the proportion of mediation effect was 10.2% and 8.9%, respectively. MR results demonstrated that TG has a causal effect on serum urate (β = 0.22, 95% CI: 0.15, 0.29; p = 2.28×10–10.) and its proportion of mediation effect was 14.1%. TC, HDL, and LDL are not the mediators in the pathway of BMI on serum urate in MR estimates. Conclusion To a certain extent, TG mediates the effect of BMI on serum urate, and the risk of gout may be reduced by controlling both BMI and TG.